About orientation dependence of physico-chemical properties of HPHT diamond surfaces thermally treated in H2 and D2 environments - Manfredotti, C.; Bonino, P.; De La Pierre, Marco; Vittone, E.; Manfredotti, C. (Elsevier S.A., 2010)
Recently [1] we reported on some preliminary results on different physico-chemical properties of diamond (100), (110) and (111) surfaces hydrogenated by using molecular hydrogen only. The main conclusions were that thermal hydrogenation was as efficient as plasma one and that the creation of the conducting surface channel was activated by a larger energy on the (100) surface with respect to the other two. The reason, at least in the case of the comparison between (100) and (111) surfaces, could be either attributed to the presence of a carbon – oxygen double bond before hydrogenation in the former case [2] or to a better coverage by carbon – hydrogen bonds in the latter one. In the present work, further results on surface conductivity after hydrogenation steps carried out at different temperatures are described and discussed, in order to discriminate between purely thermal and kinetic effects. Moreover, other results are reported on diamond powders (0.25 micrometer mean size) in order to draw some qualitative and quantitative conclusions about hydrogen presence and behavior at the diamond surfaces. In order to better clarify the results, a large part of chemical measurements were performed after deuteration steps carried out using the same conditions as thermal hydrogenation.